2021
DOI: 10.1111/1462-2920.15658
|View full text |Cite
|
Sign up to set email alerts
|

Iron corrosion by methanogenic archaea characterized by stable isotope effects and crust mineralogy

Abstract: Carbon and hydrogen stable isotope effects associated with methane formation by the corrosive archaeon Methanobacterium strain IM1 were determined during growth with hydrogen and iron. Isotope analyses were complemented by structural, elemental and molecular composition analyses of corrosion crusts. During growth with H 2 , strain IM1 formed methane with average δ 13 C of À43.5‰ and δ 2 H of À370‰. Corrosive growth led to methane more depleted in 13 C, with average δ 13 C ranging from À56‰ to À64‰ during the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Sulfate-reducing microorganisms are of interest to the fossil fuel industry because microbial souring of oil and gas fields from H 2 S can occur from the injection of sulfate-rich seawater, fueling active sulfate reduction (116). The coupling of nonmethane alkane degradation to metal reduction in cultured microorganisms has not yet been confirmed, but the corrosion of steel by anaerobic microorganisms is a well-known phenomenon apparently linked to oil-field microbial communities (124,135). In the absence of sulfate, some alkane-degrading bacteria from the former class Deltaproteobacteria form syntrophic consortia with methanogens, resulting in net methanogenesis as a terminal electron-accepting process (56,125,155).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfate-reducing microorganisms are of interest to the fossil fuel industry because microbial souring of oil and gas fields from H 2 S can occur from the injection of sulfate-rich seawater, fueling active sulfate reduction (116). The coupling of nonmethane alkane degradation to metal reduction in cultured microorganisms has not yet been confirmed, but the corrosion of steel by anaerobic microorganisms is a well-known phenomenon apparently linked to oil-field microbial communities (124,135). In the absence of sulfate, some alkane-degrading bacteria from the former class Deltaproteobacteria form syntrophic consortia with methanogens, resulting in net methanogenesis as a terminal electron-accepting process (56,125,155).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as no charging of the crust under the electron beam was observed, it can be concluded that its electrical resistance was low, probably because of the presence of FeS which is known to be electrically conductive (Venzlaff et al, 2013). In fact, even with biogeochemical processes generating solely non-conductive carbonate minerals such as iron corrosion by methanogens, a low sulphide concentration in comparison to those generated here was enough to generate a conductive crust due to the formed FeS (Tamisier et al, 2022). Also, competition between the microorganisms to access the electron source did not occur since after 36 days of incubation, the coupons surface were not densely colonised by cells to suggest such competition.…”
Section: Panelmentioning
confidence: 65%
“…The carbon isotope composition of CO 2 was determined with a GC-combustion isotope ratio mass spectrometer (GC-IRMS, Thermo Finnigan MAT 253 253, Bremen, Germany). The isotope composition of soil organic matter was determined with an Elemental Analyzer coupled to isotope ratio mass spectrometer (Thermo Fisher Scientific, Bremen, Germany) (Girardi et al 2013) Isotope data were reported in delta notation as described in Tamisier and colleagues (Tamisier et al 2022).…”
Section: Methodsmentioning
confidence: 99%